2022
DOI: 10.1210/endocr/bqac134
|View full text |Cite
|
Sign up to set email alerts
|

RhoB Promotes Endometrial Stromal Cells Decidualization Via Semaphorin3A/PlexinA4 Signaling in Early Pregnancy

Abstract: Endometrial decidualization refers to a series of morphological changes and functional remodeling of the uterine endometrium to accept the embryo under the effect of estrogen and progesterone secreted by ovaries after ovulation. During decidualization, endometrial stromal cells (ESCs) proliferate and differentiate into decidual stromal cells (DSCs), undergoing cytoskeletal rearrangement-mediated morphological changes and expressing decidualization markers, such as insulin-like growth factor-binding protein-1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…1F, S2; Methods). Examining the function of the top DEGs across species revealed key actors of endometrial receptivity (PGR, ESR1, Asgr2, RPLP2) (Wetendorf et al 2017; Cha, Sun, and Dey 2012; Forde et al 2011; Manohar et al 2014), embryo implantation (KLK11, TPPP3, CDC20B, Gper1) (Wetendorf et al 2017; Cha, Sun, and Dey 2012; Fernando et al 2006; Kolkova et al 2010; Yan and Clarke 2017), decidualization (TPPP3, Gper1, GJA1, PLXNA4, C1rb, Ceacam10) (Kaya et al 2015; Garrido-Gomez et al 2021; Shukla et al 2019; Kolkova et al 2010; Yu et al 2017; Manley et al 2020; Xu et al 2022; Sones et al 2018; Finkenzeller et al 2003), pregnancy outcomes (GSTA3, Kcnj1) (Garrido-Gomez et al 2021; 2017; Lundgren et al 1997) and endometrial dynamic changes during the menstrual cycle (ESR1, PGR, DEUP1, LGALS3) (Gleeson et al 1993; Spassky and Meunier 2017; Okumu et al 2011). Additionally, in each species, around 75% of genes differentially expressed under E2 treatment were also DEGs after E2+P4 treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1F, S2; Methods). Examining the function of the top DEGs across species revealed key actors of endometrial receptivity (PGR, ESR1, Asgr2, RPLP2) (Wetendorf et al 2017; Cha, Sun, and Dey 2012; Forde et al 2011; Manohar et al 2014), embryo implantation (KLK11, TPPP3, CDC20B, Gper1) (Wetendorf et al 2017; Cha, Sun, and Dey 2012; Fernando et al 2006; Kolkova et al 2010; Yan and Clarke 2017), decidualization (TPPP3, Gper1, GJA1, PLXNA4, C1rb, Ceacam10) (Kaya et al 2015; Garrido-Gomez et al 2021; Shukla et al 2019; Kolkova et al 2010; Yu et al 2017; Manley et al 2020; Xu et al 2022; Sones et al 2018; Finkenzeller et al 2003), pregnancy outcomes (GSTA3, Kcnj1) (Garrido-Gomez et al 2021; 2017; Lundgren et al 1997) and endometrial dynamic changes during the menstrual cycle (ESR1, PGR, DEUP1, LGALS3) (Gleeson et al 1993; Spassky and Meunier 2017; Okumu et al 2011). Additionally, in each species, around 75% of genes differentially expressed under E2 treatment were also DEGs after E2+P4 treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, SEMA3A and SEMA3C expression is markedly increased in women with endometriosis [ 32 ]. SEMA3A was found in greater amounts in the glandular epithelial cells in peritoneal endometriosis and deep infiltrating endometriotic lesions of the uterosacral ligament [ 33 ]. This indicates that SEMA3A, as a nerve-repellent factor, may be responsible for the altered sympathetic innervation of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, high SEMA3C levels have been found at the maternal-fetal-placental interface during the first trimester of gestation [39], and SEMA3F, SEMA3B, and NRP2 are overexpressed in the placenta of women with preeclampsia [37,40]. Interestingly, Xu et al (2022) [33] revealed that the expression of SEMA3A was decreased in the decidua of patients who experienced unexplained spontaneous miscarriage. This finding suggests that SEMA3A may have a positive impact on embryo implantation during pregnancy and likely implies that SEMA3A has an impact on aspects of reproduction that involve fetal implantation and continuation of pregnancy.…”
Section: Discussionmentioning
confidence: 99%